Writing on the job best practices for communicating in the digital age - Coven, Martha B., 1972- (Princeton University Press, 2022)
"Based on her course at the Princeton University School of Public and International Affairs, Martha Coven presents a crisp, brief, up-to-date introduction to clear and compelling writing for future professionals. Coven covers the basics of developing a professional style and writing and revising first and successive drafts. She then covers common types of professional writing, including correspondence, memos, proposals, plans, and reports, critical feedback and cover letters. Incorporating the growing significance of statistics and other quantitative values in professional prose, Coven then turns to writing about numbers, data visualization, and slide decks. And reflecting the need for professionals to address public audiences, she concludes with coverage of instructions and forms, writing for the media, commentary, and public speaking. Coven offers advice with concrete examples and templates. She also provides guidance on how formal or informal to allow your language to be, and how to strike the right tone so your message gets heard. Coven emphasizes the "Bottom Line Up Front" approach used by the U.S. military to ensure efficient communications, by which she stresses the importance of beginning with your big idea or claim. The book stresses how a clear communications culture improves the functioning of any organization"--